2019
DOI: 10.15244/pjoes/102367
|View full text |Cite
|
Sign up to set email alerts
|

Changes of Extracellular Polymeric Substance (EPS) during Microcystis Aeruginosa Blooms at Different Levels of Nutrients in a Eutrophic Microcosmic Simulation Device

Abstract: The outbreak of cyanobacterial blooms in water can cause serious harm to water supply safety and human health, which has become one of the major water environmental problems in the present world. In this paper, the representative Microcystis aeruginosa blooms were studied by the eutrophic microcosmic simulation device between natural lake system and test in laboratory scale. Toxic Microcystis aeruginosa FACHB-905 and non-toxic Microcystis aeruginosa FACHB-469 were used to simulate algal blooms in different nut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Wang et al (2020) suggest that proteins may be transferred from the inner layer (TB-EPS) to the outside of the cell (LB-EPS and SB-EPS). They also observed a decrease in protein content in TB-EPS in the death phase, whereas the protein content was comparable during the logarithmic growth phase in all EPS fractions [11].…”
Section: Characteristics Of Extracellular Polymeric Substancesmentioning
confidence: 89%
“…Wang et al (2020) suggest that proteins may be transferred from the inner layer (TB-EPS) to the outside of the cell (LB-EPS and SB-EPS). They also observed a decrease in protein content in TB-EPS in the death phase, whereas the protein content was comparable during the logarithmic growth phase in all EPS fractions [11].…”
Section: Characteristics Of Extracellular Polymeric Substancesmentioning
confidence: 89%
“…Generally, the EPS productivity of microalgae increases under stressful conditions, such as high light sources or temperatures ( Babiak and Krzemińska, 2021 ), and Wang et al (2019) reported that s-EPS production becomes active even in limited nutritional environments. In this study, Chlamydomonas sp.…”
Section: Resultsmentioning
confidence: 99%
“…affected the release of EPS. Wang et al (2019) explained that the production of b-EPS does not directly affect the weight of biomass; however, the stable protein content in b-EPS builds a crosslinked network to maintain the internal biological membrane structure, induces rapid biosynthesis of EPS polysaccharides, and enhances microbial adhesion. Arcila and Buitrón (2017) demonstrated that an increase in the protein/polysaccharide (PN/PS) ratio of EPS has a positive effect on the formation of flocs and granules in microalgae-bacteria aggregates.…”
Section: Resultsmentioning
confidence: 99%
“…Although the daily climate changed and environmental conditions were different, the temperature, light intensity, wind speed, and weather were basically the same for each experimental jar in the sunroom. The nutrient ratios in the culture medium for bloom simulation of Microcystis aeruginosa and simulated culture device were the same as in our previous study [24]. A total of 330 temperature data were detected, with an average of 32.0 • C and a temperature range of 26.6-36.8 • C. And the light intensity ranges from 1300-60,500 Lux, with an average of 20,044 Lux.…”
Section: Culture Conditionsmentioning
confidence: 99%
“…Like ultraviolet spectroscopy, three-dimensional fluorescence spectroscopy can also obtain many indices at once. In addition to the humification index (HIX) and the freshness index (β:α) mentioned above, the excitation-emission matrix (EEM) contours and fluorescence intensity scores can also be obtained [24]. These two spectral analysis methods have high testing rates, can be set up for multi-channel instantaneous multi-point acquisition, and can provide output in real-time.…”
Section: Changes Of Three-dimensional Fluorescence Indices In the Process Of Algal Bloomsmentioning
confidence: 99%